STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA DALAM MENERAPKAN PELAYANAN PRIMA DI PERPUSTAKAAN PERGURUAN TINGGI (DI PERPUSTAKAAN STKIP PGRI JOMBANG): Studi Kasus Di Perpustakaan STKIP PGRI Jombang - Siti Munawaroh Muna; Lilis Muflicha (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
In an effort to increase the integrity value of an agency, adequate and qualified human resources are needed to be able to advance various institutions, including libraries. Libraries must always be developed and improved so that they can always provide satisfaction to their users and human resources in the library are required to provide service excellence to librarians in order to meet the needs of these users. However, there are still some users who do not understand the implementation of excellent service in the library, as a result, it is necessary to develop library human resources carried out by an agency. One of the libraries that implements HR development is the STKIP PGRI JOMBANG library. STKIP PGRI JOMBANG library always strives to share capabilities based on librarians or library staff in order to be able to advance the STKIP PGRI JOMBANG library into a superior university library. The purpose of this research is to determine the strategy of developing library human resources in implementing excellent service in the STKIP PGRI JOMBANG library. The method used in this research is to use a qualitative approach using data collection techniques using interviews and observations. The results of this study indicate that the HR strategy applied in the STKIP PGRI JOMBANG library includes further studies of formal and non-formal education, training, rotation,and participation in librarianship activities such as scientific meetings, seminars, workshops, librarianship competitions, and call for papers.